Why Target Communities Remain Subjects Rather than Partners of Development Agencies in Integrated Conservation and Development Projects in Latin America - Busck-Lumholt, Louise Marie; Corbera, Esteve; Mertz, Ole (European journal of development research, 2025)
Despite repeated calls for locally anchored Integrated Conservation and Development Projects (ICDPs), the decision-making authority of targeted Indigenous Peoples and Local Communities (IPLCs) remains limited. This paper is grounded on an Institutional Logics perspective to examine the role of major development agencies—the World Bank (WB), the United States Agency for International Development (USAID), the Inter-American Development Bank (IDB), and the German Development Bank (KfW)—in perpetuating this challenge. Interviews with project managers in the Latin American and Caribbean (LAC) region reveal complex internal hierarchies, risk-focus, high performance pressure, a “better than nothing” rationale, and a hands-off approach to community participation. We argue that these tendencies are rooted in organisational structure and individual mentalities that constitute a project management logic, which in turn raises concerns about the ability and willingness of development agencies to foster local project ownership of ICDPs. The paper calls for the international donor community to reflect on and transform such management logic, and to allocate more substantial decision-making power and resources to local representatives. Malgré les appels répétés pour des Projets Intégrés de Conservation et de Développement (en anglais, “Integrated Conservation and Development Projects”, ICDPs) ancrés localement, l'autorité décisionnelle des Peuples Autochtones et des Communautés Locales (en anglais, “Indigenous Peoples and Local Communities”, IPLCs) ciblés reste limitée. Ce document est basé sur une perspective de Logiques Institutionnelles pour examiner le rôle des principales agences de développement—la Banque Mondiale (BM), l'Agence des États-Unis pour le Développement International (USAID), la Banque Interaméricaine de Développement (BID), et la Banque Allemande de Développement (KfW)—dans la perpétuation de ce défi. Des entretiens avec des chefs de projet dans la région Amérique Latine et Caraïbes (ALC) révèlent des hiérarchies internes complexes, un focus sur le risque, une forte pression de performance, une logique de "mieux que rien", et une approche détachée de la participation communautaire. Nous soutenons que ces problèmes sont enracinés dans la structure organisationnelle et les mentalités individuelles qui constituent une logique de gestion de projet, qui à son tour soulève des préoccupations quant à la capacité et la volonté des agences de développement à favoriser l'appropriation locale des ICDPs. Le document appelle la communauté internationale des donateurs à réfléchir sur et à transformer une telle logique de gestion, et à attribuer plus de pouvoir décisionnel substantiel et de ressources aux représentants locaux. A pesar de los repetidos llamados a Proyectos Integrados de Conservación y Desarrollo (en inglés, “Integrated Conservation and Development Projects”, ICDPs) localmente anclados, la autoridad de toma de decisiones de los Pueblos Indígenas y Comunidades Locales (en inglès, “Indigenous Peoples and Local Communities”, IPLCs) objetivo sigue siendo limitada. Este documento se basa en una perspectiva de Lógicas Institucionales para examinar el papel de las principales agencias de desarrollo—el Banco Mundial (BM), la Agencia de los Estados Unidos para el Desarrollo Internacional (USAID), el Banco Interamericano de Desarrollo (BID), y el Banco Alemán de Desarrollo (KfW)—en perpetuar este desafío. Las entrevistas con los gerentes de proyectos en la región de América Latina y el Caribe (ALC) revelan complejas jerarquías internas, enfoque en riesgos, alta presión de rendimiento, una lógica de "mejor que nada", y un enfoque de no intervención en la participación comunitaria. Sostenemos que estos problemas están arraigados en la estructura organizativa y en las mentalidades individuales que constituyen una lógica de gestión de proyectos, que a su vez plantea preocupaciones sobre la capacidad y la voluntad de las agencias de desarrollo para fomentar la propiedad local de los ICDPs. El documento pide a la comunidad internacional de donantes que reflexione y transforme dicha lógica de gestión, y que asigne un poder de toma de decisiones y recursos más sustanciales a los representantes locales.